Dieulafoy Lesion in the Ascending Colon Presenting with Gastrointestinal Bleeding and Severe Anemia Complicated by a Coexisting Severe Resistant Chronic Idiopathic Thrombocytopenic Purpura - Sherif Ali Eltawansy; Brag Thyagarajan; Nadeem Baig (Case Reports in Gastrointestinal Medicine)
Background. GI (gastrointestinal) bleeding can be due to a variety of etiologies ranging from being common like bleeding peptic ulcer disease or esophageal varices. One of the rarely documented causes is the Dieulafoy lesion which is known as an abnormally large ectatic artery that penetrates the gut wall, occasionally eroding through the mucosa causing massive bleeding. In addition to that, we refer to the uncommon presentation of Dieulafoy lesion itself as it is well known to be found in the stomach, esophagus, duodenum, and jejunum but not the ascending colon as in our case. The patient had a coexisting ITP (idiopathic thrombocytopenic purpura) that was resistant to different therapies. Case Report. We report a case of a 48-year-old Egyptian female known for chronic ITP resistant to treatment. The patient presented with bright red bleeding per rectum and severe life threatening anemia. Endoscopic study showed a Dieulafoy lesion. Endoscopic clipping was successful in controlling the bleeding. Conclusion. Dieulafoy lesion is a rare reason for GI bleeding and can present in common or unexpected places. Also extreme caution should be used in patients with bleeding tendency due to different reasons, like ITP in our case.